Factors Affecting Employee Performance: A Conceptual Study on the Drivers of Employee Engagement - Pandita, Deepika; Bedarkar, Madhura (Prabandhan: Indian Journal of Management, 2015)
Employee Engagement, as a concept, has been gaining significance since the past 10 years. Organizations today consider engaged employees as strategic partners in their businesses. The concept of employee engagement has now gained even more prominence, since many drivers have been identified, which impact employee performance and well-being at the workplace. As companies across industries strive to survive and rise above the stiff competition, physical and mental well-being of employees will be one of the important aspects that HR managers need to focus on. Hence, employee engagement is today seen as a powerful source of competitive advantage, especially in the turbulent times. The present study explored the concept of employee engagement and also throws light on key drivers of employee engagement by analyzing specifically four drivers, namely communication, work-life balance, leadership, and organizational culture. Furthermore, this study also analyzed how these drivers impacted the level of employee performance and well-being at the workplace. The existing literature on drivers of employee engagement indicated that there is paucity of research on these four drivers and their impact on employee engagement. Thus, we focused on these four specific and less researched drivers.